Effect of Business Capital and Labor on Income with Credit as Moderating Variables on Traders at Blauran Market in Palangka Raya City - Agustina (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2020)
This study aims to determine: (1) the effect of capital on the income of traders at Blauran Market in Palangka Raya City, (2) the effect of labor on the income of traders in Blauran Market in Palangka Raya, (3) the effect of credit on the income of traders in the Blauran market. in the city of Palangka Raya.nThe research method used in this research is a quantitative method. The data used is primary data. Data collection techniques in the form of a questionnaire (questionnaire) with a sample of 89 respondents. The data analysis technique used is multiple linear regression analysis and hypothesis testing using the IBM SPSS 26 program. The results show that business capital and labor have a positive effect on income, credit moderates the effect of business models on income, and credit does not moderate the effect of labor on the income of traders at Blauran Market in Palangka Raya City. Sara that can be given in this study is to increase the income of Blauran Market traders in Palangka Raya City. Merchants should increase working hours so that the income earned is higher.